Alkali-silica reaction in concrete: Mechanisms, mitigation and test methods. (20th October 2019) - Figueira, R.B.; Sousa, R.; Coelho, L.; Azenha, M.; de Almeida, J.M.; Jorge, P.A.S.; Silva, C.J.R.
Graphical abstract: Highlights: Review of the most recent and relevant achievements concerning ASR process. Conditioning factors, diagnostic and preventive measures of ASR were debated. Proper models to monitor ASR is a major concern for concrete service life prediction. Several efforts have been devoted in understanding the fundamentals of ASR. Abstract: In the last few decades, the alkali–silica reaction (ASR) has been reported as one of the major concrete concerns regarding durability, leading to high maintenance and reconstruction costs. The occurrence of ASR in numerous concrete infrastructures all over the world points to the need for research regarding measures for its detection in an initial stage (and further mitigation) either in new or existing structures. Furthermore, the chemical and physical mechanisms for ASR remain poorly understood. This lack of knowledge leads to incapacity to assess risk, cost-effectively predict service life, and efficiently mitigate the deterioration process due to ASR in concrete structures. This manuscript aims to review the most recent and relevant achievements and the existing knowledge concerning the reaction mechanisms of ASR. Additionally, this manuscript is focused on the conditioning factors, diagnostic and prognostic methodologies, preventive measures and test methods (including their limitations) of ASR conducted at an academic level. The perspectives for future research challenges are also identified and debated.